Financial Performance as Mediator on the Impact of Investment and Financial Decisions on Stock Price and Future Profit: The Case of the Jordanian Financial Sector - Al-Slehat, Zaher Abdel Fattah (International Journal of Economics and Financial Issues, 2020)
The current study investigates the effect of investment and financial decisions on stock prices and future profits in the presence of financial performance as an intermediate variable. Thus, the case of the Jordanian banking and insurance sector is analysed. The sample includes 13 banks and 10 insurance companies from 2009 to 2018. A structural equation modeling analysis is conducted using the AMOS 23 software to test the hypotheses and validate the model. Financial decision exhibits no effect on future profits and stock prices, whereas investment decision affects future profits and stock prices. Financial performance is considered a mediator in the effect between financing decision and future profits. By contrast, financial performance fails to mediate the impact of financial decision and stock prices. In addition, it cannot mediate the effect of investment decision on future profits and stock prices. Keywords: Investment Decision, Financial Decision, Financial performance, Stock Price, Future Profit JEL Classifications: G1, G2, G11 DOI: https://doi.org/10.32479/ijefi.9520